Different Techniques for Simultaneously Increasing the Penetration Level of Rooftop PVs in Residential LV Networks and Improving Voltage Profile - Safitri, N.; Shahnia, Farhad; Masoum, Mohammad Sherkat (Institute of Electrical and Electronics Engineers (IEEE), 2014)
Utilization of rooftop photovoltaic cells (PVs) in residential feeders without controlling their ratings and locations may deteriorate the overall grid performance including power flows, losses and voltage profiles. This paper investigates different methods for regulating the voltage profile and reducing the voltage unbalance at low voltage residential feeders. The algorithm considers reactive power exchange and active power curtailment of the single-phase rooftop PVs. In addition, it is assumed that the distribution transformers have on-load tap changers and can automatically control the voltage to prevent voltage rise in the feeder. The main objectives of the discussed methods are to regulate the voltage profiles and reduce the voltage unbalance. MATLAB-based simulation results demonstrate effectiveness of the discussed approaches.